ANALISIS MODEL CAMEL DAN ALTMANâS Z-SCORE DALAM MEMPREDIKSI KEBANGKRUTAN BANK UMUM DI INDONESIA (STUDI PADA BANK UMUM YANG TERCATAT DI (Jurnal Tepak Manajemen Bisnis, 2014)
Analyzing CAMEL Model and Altmanâs Z-score in the Prediction of Public Bank Bankruptcy in Indonesia(A case study public bank case registered in Indonesia Stock Exchange during the period of 2007 â 2011), underthe supervision of Yulia Efni and Gusnardi.The present research seeks to find out the accuracy of CAMEL modeland Altmanâs Z-score to predict the bankruptcy of Indonesian public banks ( a case study of public banksregistered in Indonesia Stock Exchange in the period of 2007 â 2011.The research used secondary data, that is,the annual bank financial statements in the period of 2007 â 2011. The population included all Indonesiapublic banks which are still operating and registered in Indonesia Stock Change in the period of 2007 â 2011.The sample consisted of 21 banks which were selected using a purposive sampling method.The results of logicregression model test show that there is a different accuracy of predicting using CAMEL model and Altmanâs Zscorein the prediction of the Indonesian public bank bankruptcy. The best accuracy of the bankruptcy predictionmodel is Altmanâs Z-score with 0% error types I and II, and the model classification accuracy is 100%.Key words: bank, bankruptcy, bank financial ratio